Mortality and adverse events of hemoadsorption with CytoSorb® in critically ill patients: A systematic review and meta‐analysis of randomized controlled trials. Issue 9 (18th July 2022) - Heymann, Marc; Schorer, Raoul; Putzu, Alessandro
Abstract: Background: The effects and safety of extracorporeal hemoadsorption with CytoSorb® in critically ill patients with inflammatory conditions are controversial. Methods: We performed a systematic review with meta‐analysis and trial sequential analysis (TSA) of randomized‐controlled trials to assess the mortality and safety of CytoSorb® therapy in critically ill patients with inflammatory conditions. Electronic databases were searched up to April 2022. The primary outcome was mortality at longest follow‐up and secondary outcomes included various adverse event (AE) outcomes. Conflict of interest and funding of each trial were assessed. We calculated relative risk (RR) and 95% confidence interval (CI). Results: Fourteen published ( n = 764) and 4 unpublished ( n = 111) trials were included. Eight trials were performed in medical ICU patients and 10 in complex cardiac surgery. Ten trials had significant industrial funding or an author conflict of interest. Hemoadsorption with CytoSorb® was associated with higher mortality at latest follow‐up (16 trials, n = 807, 120 of 402 [29.85%] patients in the CytoSorb® group vs. 98 of 405 [24.20%] patients in the control group, RR = 1.24 [95% CI, 1.04–1.49], p = .02, [TSA‐adjusted CI, 0.92–1.68]) and at 30‐days or in‐hospital (11 trials, n = 727; RR = 1.41 [95% CI, 1.06–1.88], p = .02, [TSA‐adjusted CI, 0.44–4.62]). Only one trial reported the definition of adverse event, while detailed results were reported in 3 trials; the risk of adverse events was not higher with CytoSorb®. Certainty of evidence ranged from low to very low. Conclusion: Low certainty of evidence showed that the use of CytoSorb® might increase mortality in critically ill patients with inflammatory conditions. Adverse events were frequent but underreported and not systematically evaluated. Industrial funding and conflict of interest were common. Considerable uncertainty about the findings does not allow firm conclusions and suggests a need for high‐quality randomized trials to clarify mortality and adverse events related to CytoSorb®. Editorial Comment: Hemoadsorption with CytoSorb® have been used in critically ill patients despite lack of high quality data from RCTs suggesting any patient‐important benefits. The findings from this systematic review and meta‐analysis suggests an increased risk of adverse events including mortality. With no apparent benefits and at the same time risk of harm, use of hemoadsorption with CytoSorb® in daily clinical practice cannot be recommended at this time.